Classroom Changes in ADHD Symptoms Following Clinic-Based Behavior Therapy - Curtis, David F.; Chapman, Stephanie; Dempsey, Jack; Mire, Sarah (Journal of clinical psychology in medical settings, 2013)
This study examined classroom behavioral outcomes for children with Attention-Deficit/Hyperactivity Disorder (ADHD) following their participation in a manualized, 10-week intervention called Family Skills Training for ADHD-Related Symptoms (Family STARS). Family STARS combined behavioral parent training (BPT) and child-focused behavioral activation therapy (CBAT). Participants were children ages 7–10 diagnosed with ADHD-Combined Type. Pre- and post-treatment teacher ratings of ADHD symptoms were compared using a single group, within-subjects research design. Intervention effectiveness was analyzed using paired-samples t -tests. Results indicated statistically significant classroom improvements for externalizing behaviors and attention problems with medium and large main effects (respectively) for the intervention. Possible implications for combining CBAT with BPT for the treatment of ADHD are discussed as well as the relevance of these results for improving the effectiveness and portability of empirically supported interventions.